Język a kultura. Komunikacja Werbalna w wybranych polskich, brytyjskich i amerykańskich programach telewizyjnych - Zięba, Anna (Investigationes Linguisticae, 2008)
This article is an attempt to analyze culture’s impact on human verbal communication. The first part combines the differences between Polish and English with the cultural dimensions described by Geert Hofstede and with Hall’s contextuality. Then, actual examples of verbal manifestations of cultural differences are given based on popular Polish, British and American TV programmes. These are talk shows: Rozmowy w toku and The Oprah Winfrey Show, dancing shows: Taniec z gwiazdami and Strictly Come Dancing, and medical dramas: Na dobre i na złe and Emergency Room. The source material on which this paper is based consists of recordings of the shows (recorded while broadcast and a Warner Bros DVD), a video sharing website YouTube and literature concerning cultural differences and their impact on language.